Does providing agricultural and nutrition information to both men and women improve household food security? Evidence from Malawi - Ragasa, Catherine; Aberman, Noora-Lisa; Mingote, Cristina Alvarez (International Food Policy Research Institute, 2017)
The International Food Policy Research Institute is leading a three-year research program to assess the state of agricultural extension and advisory services provision in Malawi in order to inform the national extension policy review and reformation of government and donor processes and programming. This research program includes a series of studies undertaken in response to a request by the Ministry of Agriculture, Irrigation and Water Development to look closely at the state of extension services provision with the intent to further strengthen the contribution of these services to food security, economic growth, and the achievement of sustainable development goals. In this paper, we examine the role of gender in various pathways to food security in Malawi, emphasizing improved access to agriculture and nutrition information along these pathways and considering the implications of gender targeting for agriculture and nutrition extension services. We propose a gendered typology of households: those with both male and female adults, those with only adult males, and those with only adult females. We take a mixed-methods approach of sequential quantitative-qualitative data collection, consisting of focus group discussions in eight districts and nationally representative household and community surveys. The results show that food insecurity is highest in male-only households. In dual-adult households, in which women are frequently tasked with attending training and meetings but have little power to implement lessons, joint access to information is a more powerful driver of food security than women’s access.